Analisis Faktor-Faktor Determinan terhadap Proses dan Capaian Prestasi Belajar Siswa Kelas II MI JA Al-Haq Kota Bengkulu - Hikmatul Munawarah; Islamiah Istikharah; Ziyyah Ul Mu'izzah Zulta; Asmara Yumarni; Asniti Karni (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
This study aims to describe the factors that influence the learning process and the learning achievement of students. This type of research is field research with a qualitative approach. The sample for this research is class IIA MI Plus Ja Al-Haq students in Bengkulu City. Data collection methods used are observation, interviews, and documentation. Data on the factors that influence the learning process and learning achievement is collected using observation sheets and interviews. The results of research in class IIA, MI Plus Ja Al-Haq Bengkulu City, show that the factors that influence the learning process and learning achievement in class IIA are individual student factors, environmental factors, teaching materials, and learning methods. While learning achievement is influenced by internal factors, which include intelligence, learning motivation, interests, and attitudes, as well as study habits, and external factors, including the physical environment, social environment, and family environment, With this research, researchers know that the factors that greatly influence the learning process and learning achievement of students in IIA MI Plus Ja Al-Haq are individuals and the environment.